Gender Representation in the Contents and Illustrations of Religious Education Textbooks - Akmansyah, Muhammad; Nurnazli; Tiarani, Fitria (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This research aims to explore gender representation in Islamic Religious Education textbooks by examining the portrayal of gender through both content and illustrations. The study investigates how gender roles and values are reflected in the Qur'an, Hadith, descriptive narratives, and visuals in the textbooks. Additionally, it explores how Islamic Education promotes gender-related values through various elements, including text, narratives, and imagery. This study uses the library research method, this study analyses gender equality in Qur'anic verses, al-Hadits, descriptive narratives, and illustrations in these textbooks. Data were collected through a literature study, including identifying and reviewing verses, gender narratives, and illustrations. Content and visual analyses were conducted to find gender representation. Each element was analyzed in depth to understand its educational and social implications. The results showed that Qur'anic verses, Hadits of the Prophet Muhammad, descriptive narratives, and illustrative images provide a strong foundation for respecting, protecting, recognizing the contributions, and valuing women's rights in all aspects of life, including education, economy, marriage, inheritance, and family relationships. This demonstrates Islamic Religious Education's commitment to gender equality and justice in treating all individuals, regardless of gender. This research, however, is still limited to religious texts and does not consider the socio-cultural context. It is recommended that future textbooks strengthen the principles of gender justice by including socio-cultural contextualization, helping learners understand its practical application.